Reward Management and Affective Commitment among Faculties in Nepalese Higher Education - Kharel, Shreekrishna (Tribhuvan University Journal, 2018)
This study tries to investigate the relationship between reward management and affective commitment in faculty in higher educational organizations. This follows a questionnaire survey of variables with a five- point likert and uses regression analysis, coefficient of variation, normality test, factor analysis and Cronbach’s alpha for analytical tools. The result shows a positive relationship between reward management and affective commitment. Hence reward management has been seemed to be beneficial for affective commitment. The sectoral sampling adequacy and number of organizations represented in survey might be the small for general implications of the results despite its analytical soundness.